Dynamics of emotions during an inquiry-based activity in experimental science education - Agen, Federico; Andreini, Claudia; Campillos, Rafael; Ezquerra, Angel (Form@re - Open Journal per la formazione in rete, 2025)
This study investigates the dynamics of emotions among pre-service science teachers during an Inquiry-Based Learning (IBL) activity. Participants, divided into Observers and Observed, reported the emotions experienced, the phases of the scientific method, and the activation levels of the Observed through an online form. The results indicate that the most frequently reported emotions were enjoyment, confusion, frustration, and satisfaction, following a characteristic sequence typical of this kind of activity. The inquiry phases showed a progression consistent with the cognitive demands of each stage. Attention and engagement consistently reflected high levels of activation, peaking at the beginning of the activity. These findings highlight the crucial role of both positive and negative emotions in learning processes and emphasize the importance of incorporating emotional awareness and regulation into teacher education programs. Dinamica delle emozioni durante un’attività di indagine in didattica delle scienze sperimentali. Questo studio esamina la dinamica delle emozioni di futuri insegnanti durante un’attività di apprendimento basato sull’indagine (IBL). I partecipanti, suddivisi in Osservatori e Osservati, hanno riportato le emozioni, le fasi del metodo scientifico e i livelli di attivazione degli Osservati tramite un modulo online. I risultati hanno mostrato che le emozioni più frequenti sono state Divertimento, Confusione, Frustrazione e Soddisfazione con una sequenza caratteristica per un’attività di questo tipo. Le fasi del metodo hanno mostrato una progressione coerente con le richieste cognitive di ciascun momento. L’attenzione e il coinvolgimento hanno indicato livelli elevati di attivazione, con un picco nelle fasi iniziali dell’attività. I risultati confermano il ruolo cruciale delle emozioni, sia positive che negative, nei processi di apprendimento e sottolineano l’importanza di integrare la consapevolezza e la regolazione emotiva nei programmi di formazione degli insegnanti.